2018
DOI: 10.1016/j.juro.2018.03.116
|View full text |Cite
|
Sign up to set email alerts
|

Performance Characteristics of Transrectal Shear Wave Elastography Imaging in the Evaluation of Clinically Localized Prostate Cancer: A Prospective Study

Abstract: Quantitative shear wave elastography via the transrectal approach accurately detected cancer foci and revealed significant differences between cancerous and benign tissue. Moreover, this technique can be used to reliably phenotype prostate cancer aggressiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 26 publications
0
52
0
Order By: Relevance
“…Of these men, 68 had positive biopsy findings, and ultrasound elastography showed excellent overall performance (AUC, 0.95; sensitivity, 96%; and specificity, 85%). Wei et al investigated a cohort of 212 men with clinically localized PCa using whole‐mount prostatectomy specimens as reference standard and found an excellent diagnostic performance as well (AUC, 0.98; sensitivity, 97%; and specificity, 68%) …”
Section: Discussionmentioning
confidence: 99%
“…Of these men, 68 had positive biopsy findings, and ultrasound elastography showed excellent overall performance (AUC, 0.95; sensitivity, 96%; and specificity, 85%). Wei et al investigated a cohort of 212 men with clinically localized PCa using whole‐mount prostatectomy specimens as reference standard and found an excellent diagnostic performance as well (AUC, 0.98; sensitivity, 97%; and specificity, 68%) …”
Section: Discussionmentioning
confidence: 99%
“…Woo et al found significant linear correlations between Gleason score and mean stiffness (r = 0.343, p = 0.002) and mean stiffness ratio (r = 0.296, p = 0.008) [38]. A study by Wei et al showed increasing stiffness by tumor grade (91.6, 102.3, and 131.8 kPa for Gleason scores 6, 7, and C 8) with benign tissue measuring 58.3 kPa [41].…”
Section: Review Of Literaturementioning
confidence: 96%
“…In a study with 60 patients, Boehm et al found that PCA (88 kPa) to be stiffer than benign tissue (42 kPa, p \ 0.001) and sensitivity, specificity, PPV, and NPV of 80.9, 69.1, 67.1, and 82.2% using a cut-off of 50 kPa [40]. A recent prospective study of 212 men showed that a cut-off of 82.6 kPa had a high sensitivity (96.8%) with specificity of 67.8% and AUC of 0.976 [41]. However, Porsch et al found poor results in a smaller number of patients (n = 10) with a cut-off of 50 kPa, producing sensitivity, specificity, and AUC of 74%, 43%, and 0.527 [42].…”
Section: Review Of Literaturementioning
confidence: 99%
“…A total of 217 published studies were identified from the datasets in accordance with our search strategy. After removing the duplicates, screening the title and abstract and carrying out further evaluation, 13 studies were identified that use SWE for diagnosis of PCa; however, two studies provided insufficient data [28,29], one study was based on a total number of patients <20 [22] and one study enrolled patients with recurrent PCa [30]; hence, 9 studies were ultimately included in our present study [9,11,[31][32][33][34][35][36][37] (fig 1). Among the included studies, the study by Ahmad et al [9] was analysed twice according to PSA groupings of 4-20 ng/ml and over 20 ng/ml.…”
Section: Selected Studies and Quality Assessmentmentioning
confidence: 99%
“…raphy can improve the detection of stiff prostatic tissues [12,13]. However, TRUS is not sufficiently sensitive or specific for biopsy procedures and whether it definitely improves the diagnostic accuracy of PCa detection remains controversial [11,14]. Hence, shear wave elastography (SWE) was introduced in guiding biopsies and for improving the detection of prostate lesions.…”
mentioning
confidence: 99%